Operational efficiency of timber skidding in Sapulut, Sabah - W Ahmad, Wan Mohamad Hafeez (2019)
Timber skidding is one of the important components in forest harvesting. The process of harvesting a forest includes all operations from cutting down trees and delivering the log to a mill, rail depot, or ship dock. Efficiency is the ability to avoid wasting materials, energy, efforts, money, and time in doing something or in producing a desired result. In forest harvesting, each of the operations conducted in the natural forest is being evaluated through details planning. For skidding operation, widely use bulldozer as a medium in transporting log to temporary log landing require attention from many sides. This is because it may affect the productivity and time consumed to do the work. The objectives of this study were i) measure the distance, time, productivity of skidding operation by crawler tractor and ii) to examine the relationship between time, distance and productivity of skidding operation by crawler tractor. Results showing relationship between volume of logs with trip cycle on average about 2.037m³ volume of log or one big log can be skidded on each trip. For relationship of distance and trip cycle, the results show the shortest distance is at 310 meters which due to efficiency productivity, and longest distance which is at 420 meters. On average, about 360 meters trail length of distance travelled by crawler tractor on each trip. Next, for speed and trip cycle graph shape distribution showing unevenness on the relationship between speed and number of trips. This could be due to describe problems as above or non-productive delay occurrence such as drinking, smoking or resting. Besides, distribution of work element on time consumption show skidding seems to consume more time compared to another process since crawler tractor workers manually doing the work. Crawler tractor took the total time to complete 5 trips per day was between 4.021 hours to 4.300 hours within distance at 310 meters to 420 meters including delay. The results of this study provide current information that could be used by the management agency in Sapulut Forest Reserve especially Forestry Department Sabah to make an improvement toward skidding operation in this type of forest.